CAPITAL STRUCTURE AS DETERMINANT OF FINANCIAL PERFORMANCE: REVIEW OF LITERATURE - Desai, Jay; Desai, Rajesh (Copernican Journal of Finance & Accounting, 2020)
One of the most critical decisions in corporate finance is to decide about the source of fund to be employed. The mix of debt – equity used to generate funds is termed as Capital Structure (CS). Research on Capital Structure and its impact on financial performance has gained momentum from the pioneering article of Modigliani and Miller (1958). Since then it has been one of the most debated and controversial aspects of corporate finance. Researchers have contributed in form of theories as well as empirical findings to study the relation between capital structure and financial performance. Current paper reviews the existing studies in the area of CS and financial performance and also propose a conceptual model that describes the interrelationship between CS and financial performance based on detailed discussion of widespread literature. This model reckons important variables of financial performance affected by CS which help research scholars in further investigation. Researchers can use this model to perform empirical testing to fill the research gaps identified and enrich the existing literature.